The Use of Discourse Markers in Kurdish EFL Undergraduate Students’ Writing: at Raparin University. (Raparin Journal of Humanities (RJH), 2025)
The current study examines discourse markers which are important language devices that enhance coherence in writing. Coherence and cohesion in Kurdish EFL Undergraduate Students’ Writing are essential components that contribute to clarity and effectiveness.  The aim of this study is to explore the extent to which Kurdish EFL undergraduate students at Raparin University, third-year morning class, utilize DMs in their writing. Moreover, to identify the difficulties that learners face and the most frequently used DMs. This study adopts Halliday and Hassan's cohesion model for the process of data analysis collected at Raparin University. For this purpose, mixed methods (quantitative and qualitative) are used in the process of data collection. As well as survey is used as a tool for this investigation. Fifty participants from Raparin University participated in answering survey questions.The results show that undergraduate students exhibit various kinds of frequency in utilizing additional types of DMs while writing an essay. Due to a lack of understanding about how to employ adversative, temporal, and causal forms of discourse markers, students overuse additional types of DMs, and their writing lacks cohesion and coherence to write an academic essay.